Development and Validation of a Research Skills Instrument for Students in the Context of Environmental Change to Support the Clean Water and Sanitation Goal - Bariroh, Ghurrotul; Sriyati, Siti; Solihat, Rini (Unnes Science Education Journal, 2025)
Research skills are an essential competencies in biology education, particularly in understanding environmental changes topic. One crucial aspect of this topic is the effort to maintain the quality of natural resources, including clean water, which aligns with Sustainable Development Goal (SDG) 6: Clean Water and Sanitation. However, there is currently no specific instrument designed to assess students’ research skills, especially in the context of environmental change related to clean water and sanitation. Therefore, this study aims to develop a multiple-choice research skills assessment instrument. The development process followed the 4D model, which includes the stages of Define, Design, Develop, and Disseminate. Data were analyzed using descriptive statistics to evaluate the validity, reliability, and feasibility of the instrument, and the results were interpreted to determine the instrument’s effectiveness in assessing students’ research skills. Expert validation results indicate that the instrument has a feasibility score of 82.55%. A field trial involving 63 students revealed that out of 26 test items, 13 were accepted, 5 required revision and 8 were rejected based on validity, reliability, difficulty level, and discrimination index analyses. Overall, the instrument is valid, reliable, and effective in measuring students’ research skills. Future research is recommended to develop more contextually relevant instruments that better reflect students’ research skills in addressing real-world challenges. Additionally, further validation in broader educational settings is necessary to ensure the instrument’s effectiveness across various instructional methods.